In situ observation of intergranular crack nucleation in a grain boundary controlled austenitic stainless steel. - Rahimi, S; Engelberg, D; Duff, J; Marrow, T (John Wiley and Sons, 2009)
Grain boundary engineering has been proposed to increase the lifetime performance of sensitized austenitic stainless steel in aggressive environments. Increased microstructure resistance is typically associated with higher fractions of twin ([sigma]3) grain boundaries, but there is uncertainty about the properties and role of other boundaries. To develop predictive models for stress corrosion crack nucleation, more information is required about how grain boundary crystallography and the orientations of the grain boundary plane and its surrounding grains affect crack development. Digital image correlation combined with electron backscatter diffraction has been used to characterize the microstructure and to observe, in situ, the nucleation and propagation of short stress corrosion cracks in thermo-mechanically processed type 304 stainless steel. The crack path and its growth rate have been determined and are found to be influenced by the microstructure. Copyright 2009 The Royal Microscopical Society.